Pengaruh Stres dengan Perilaku Olahraga Pada Mahasiswa Fakultas Kedokteran Selama Pandemi Covid-19 - Ibnu Aji Setyawan; Octa Reni Setiawati; Akhmad Kheru Dharmawan; Woro Pramesti (Jurnal Ilmiah Kesehatan Sandi Husada, 2021)
Introduction; The current Covid-19 pandemic is one of the major health crises for individuals in all countries, continents, RAS, and socio-economic groups. Objectives; know the effect of stress on exercise behavior during the Covid-19 pandemic. Method; quantitative research with analytic design and cross-sectional approach. The measuring instruments used were the DASS42 questionnaire (Depression Anxiety Stress Scales 42) and the exercise intensity questionnaire. Result; Of the 60 samples studied, it was found that the largest age frequency distribution in this study was 30 people (50%), the highest gender frequency was 32 women (53.3%), the level of stress that was most often found. namely moderate stress as many as 21 people (35%), the frequency of sports behavior that was mostly found with low intensity was 25 people (41.7%). Conclusion: There is no effect of stress on exercise behavior on students when they enter the covid-19 medical faculty